Current status of hypertension management operation mechanisms in Chinese mainland and their impact on prevention and control effects: an analysis on official documents - Huihui HUANGFU; Qinwen YU; Peiwu SHI; Qunhong SHEN; Zhaoyang ZHANG; Zheng CHEN; Chuan PU; Lingzhong XU; Zhi HU; Anning MA; Zhaohui GONG; Tianqiang XU; et al. (Zhongguo gonggong weisheng)
ObjectiveTo evaluate the current status of hypertension prevention and control management operation mechanisms in Chinese mainland, explore the impact of their improvement on hypertension prevention and control effects, and provide a reference for enhancing hypertension prevention and control management. MethodsPolicy documents related to hypertension prevention and control from January 1 2000 to December 31, 2018 in 31 provinces (municipalities and autonomous regions) in Chinese mainland were collected. The current status of hypertension prevention and control management operation mechanisms in Chinese mainland was systematically evaluated according to the appropriate public health system evaluation model and standard. A logistic regression model was used to analyze the impact of the improvement of management operation mechanisms on hypertension prevention and control effects. ResultsIn 2018, the appropriateness of hypertension prevention and control management operation mechanisms in Chinese mainland was 43.68%, with an increase of 21.64% compared to 2000, but there was still a gap of 48.61% from the appropriate standard. Among them, the appropriateness of coordination and incentive mechanisms was the lowest (14.03%), and the appropriateness of planning and evaluation mechanisms was the highest (63.04%). In terms of specific positioning, the coverage of medium and long-term plans (100.00%) and the completeness of content and form (94.45%) were relatively high, while the feasibility of management mechanisms was only 9.76%. The results of logistic regression analysis showed that the improvement of management operation mechanisms helped control blood pressure in hypertensive patients (OR = 1.012, P = 0.007) and maintain the stability of patients’ blood pressure (OR = 1.010, P = 0.029). Conclusion From 2000 to 2018, the construction of hypertension prevention and control management mechanisms in Chinese mainland tended to be improved, effectively promoting the improvement of hypertension prevention and control management levels. However, it is still necessary to further establish and improve coordination and incentive mechanisms and clarify the division of departmental responsibilities.